Emergence of Lassa Fever Disease in Northern Togo: Report of Two Cases in Oti District in 2016. (17th December 2017) - Patassi, Akouda Akessiwe; Landoh, Dadja Essoya; Mebiny-Essoh Tchalla, Agballa; Halatoko, Wemboo Afiwa; Assane, Hamadi; Saka, Bayaki; Naba, Mouchedou Abdoukarim; Yaya, Issifou; Edou, Kossi Atsissinta; Tamekloe, Tsidi Agbeko; Banla, Abiba Kere; Davi, Kokou Mawule; et al.
Abstract : Background . Lassa fever belongs to the group of potentially fatal hemorrhagic fevers, never reported in Togo. The aim of this paper is to report the first two cases of Lassa fever infection in Togo. Case Presentation . The two first Lassa fever cases occurred in two expatriate's health professionals working in Togo for more than two years. The symptoms appeared among two health professionals of a clinic located in Oti district in the north of the country. The absence of clinical improvement after antimalarial treatment and the worsening of clinical symptoms led to the medical evacuation. The delayed diagnosis of the first case led to a fatal outcome. The second case recovered under ribavirin treatment. Conclusion . The emergence of this hemorrhagic fever confirms the existence of Lassa fever virus in Togo. After a period of intensive Ebola virus transmission from 2013 to 2015, this is an additional call for the establishment and enhancement of infection prevention and control measures in the health care setting in West Africa.